Impact of climate change on agriculture in Irrigation District 005, Chihuahua, Mexico - Lucero López, Claudia Yessenia; Castruita Esparza, Luis Ubaldo; Legarreta González, Martin Alfredo; Olivas García, Jesús Miguel; Uranga Valencia, Luisa Patricia; Luján Álvarez, Concepción (Revista Mexicana de Ciencias Agrícolas, 2022)
It is expected that the sector most economically affected by climate change is agriculture, being affected by the decrease in economic income. The objective of the research was to know the impact of the climate change in the agriculture in Irrigation District 005 located in the state of Chihuahua. This, through the application of surveys in the year 2020. Chi-square tests were performed, obtaining that, of the respondents: 40% [X2 (1,38.32) p
Keywords: adaptation; agriculture; climatology; mitigation